Tolak Bala and Islamic Aqidah Understanding: Revealing Dilemmas in the Religious Practices of Javanese Moslem Society - Amanah, Khotimatul (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The practice of rejecting reinforcements is an important part of religious traditions that often involve rituals that developed locally. This research aims to investigate the dilemma that arises in Javanese Muslim religious practices related to the concept of rejecting evil and understanding Islamic aqidah. The method used in this research is qualitative, where data is collected through interviews with informants, and is supported by the relevance of related literature. The research results show that in daily religious practice, the Javanese Muslim community often faces a dilemma between the concept of repelling evil and understanding fundamental Islamic beliefs. Although generally accepting the concept of Islamic aqidah, some traditional practices such as rejecting reinforcements are still maintained in Javanese culture. This research contributes to the literature on religion and culture, by describing the complexity of religious practices in Javanese society and the conflicts that arise between local traditions and Islamic religious teachings. In addition, this research also provides a basis for further reflection on how Islam is interpreted and practiced in diverse local cultural contexts.